Random Lasing with Systematic Threshold Behavior in Films of CdSe/CdS Core/Thick-Shell Colloidal Quantum Dots - Gollner, Claudia; Ziegler, Johannes; Protesescu, Loredana; Dirin, Dmitry N.; Lechner, Rainer T.; Fritz-Popovski, Gerhard; Sytnyk, Mykhailo; Yakunin, Sergii; Rotter, Stefan; Amin, Amir Abbas Yousefi; Vidal, Cynthia; Hrelescu, Calin; et al. (Acs Nano, 2015)
While over the past years the syntheses of colloidal quantum dots (CQDs) with core/shell structures were continuously improved to obtain highly efficient emission, it has remained a challenge to use them as active materials in laser devices. Here, we report random lasing at room temperature in films of CdSe/CdS CQDs with different core/shell band alignments and extra thick shells. Even though the lasing process is based on random scattering, we find systematic dependencies of the laser thresholds on morphology and laser spot size. To minimize laser thresholds, optimizing the film-forming properties of the CQDs, proven by small-angle X-ray scattering, was found to be more important than the optical parameters of the CQDs, such as biexciton lifetime and binding energy or fluorescence decay time. Furthermore, the observed systematic behavior turned out to be highly reproducible after storing the samples in air for more than 1 year. These highly reproducible systematic dependencies suggest that random lasing experiments are a valuable tool for testing nanocrystal materials, providing a direct and simple feedback for further development of colloidal gain materials toward lasing in continuous wave operation. © 2015 American Chemical Society.
Keywords: exciton-exciton interactions; giant shell quantum dots; plasmonics; random lasing; successive ion layer adsorption and reaction